Investigation on Gaseous and Particle Mass Emissions from Automatically Fired Small Scale Heating System under Laboratory Conditions - Md. Obaidullah; Svend Bram; Jacques De Ruyck De Ruyck (International Journal of Renewable Energy Development, 2018)
This study presents the experimental results on gaseous and particle mass emissions obtained from a bottom feed pellet stove of 2.5 kW output in part load heat and 5 kW output in nominal heat. The experiments were conducted in a stove manufacturing plant in the southern part of Belgium. Two combustion experiments (A and B) in part load heat output and four experiments (C, D, E and E) in nominal load were performed at three combustion phases: startup, combustion and burnout phase. The pellet stove was operated in different fan speeds varied from 900 rpm to 1250 rpm for the combustion experiments. Experiments A and B were operated with low speed fan, C and D with medium speed fan, E and F with high speed fan. The emissions results include CO2, CO, O2 and particle mass concentrations are presented in this study. A performance analysis in terms of combustion efficiency together with different losses of the pellet stove is also discussed. The experimental results show that CO emissions obtained from the main combustion phase of the part load heat output experiments varied from 1215 mg/Nm3 to 1450 mg/Nm3, while in the nominal load heat output varied from 50 mg/Nm3 to 145 mg/Nm3. Also, the results show that CO emissions in the burnout phase from all the experiments were significantly higher than that in the startup phase followed by the combustion phase. The finding shows that higher CO emissions in the startup and burnout phase have influence on the total CO emissions. Particle mass emissions obtained from the combustion experiments operated with high fan speed varied from 10-15 mg/Nm3 respectively and were much lower than the required limit value of standard EN14785 and other works. The combustion efficiency obtained from all the experiments for the low speed fan, medium speed fan and high speed fan was 92.8±1.2 %, 92.4±1.1 % and 92.7±1.2 % respectively and satisfied the required limit value of the standard.Article History: Received Sept 12th 2017; Received in revised form March 17th 2018; Accepted April 26th 2018; Available onlineHow to Cite This Article: Obaidullah, M., Bram, S. and De Ruyck, J. (2018) Investigation on Gaseous and Particle Mass Emissions from Automatically Fired Small Scale Heating System under Laboratory Conditions. Int. Journal of Renewable Energi Development, 7(2), 111-121.https://doi.org/10.14710/ijred.7.2.111-121